Getting cars off the road: the cost-effectiveness of an episodic pollution control program - Maureen L. Cropper; Yi Jiang; Anna Alberini; Patrick Baur (Fondazione Eni Enrico Mattei (FEEM), 2010)
Ground level ozone remains a serious problem in the United States. Because ozone non-attainment is a summer problem, episodic rather than continuous controls of ozone precursors are possible. We evaluate the costs and effectiveness of an episodic scheme that requires people to buy permits in order to drive on high ozone days. We estimate the demand function for permits based on a survey of 1,300 households in the Washington, DC metropolitan area. Assuming that all vehicle owners comply with the scheme, the permit program would reduce VOCs by 50 tons and NOx by 42 tons per Code Red day at a permit price of 75. Allowing for non-compliance by 15% of respondents reduces the effectiveness of the scheme to 39 tons of VOCs and 33 tons of NOx per day. The cost per ozone season of achieving these reductions is approximately 9 million (2008 USD). This compares favorably with permanent methods of reducing VOCs that cost 645 per ton per year.
Keywords: Q52; Q53; Q58; 330; Ground-Level Ozone; Episodic Pollution Control Schemes; Mobile Sources; Volatile Organic Compounds (Vocs); Cost Per Ton of Vocs Removed